Exploring the Intersection of Violence, Disability, and Religion: a Quantitative Study on Children With Disabilities in Multicultural North Macedonia” - Georgievska, Sofija; Stanojkovska Trajkovska, Natasha; Duev, Ratko (Akademija za humani razvoj/College of Human Development Fakultet za diplomatiju i bezbednost/ Faculty of Diplomacy and Security Beograd, Srbija, 2024)
This study delves into the intersection of violence, disability, and religion within the diverse and multicultural landscape of North Macedonia, focusing on the experiences of children with disabilities who are particularly vulnerable to various forms of violence. The research aims to shed light on how cultural and religious factors influence the prevalence and impact of both primary and secondary traumatization and victimization among these children. Utilizing a sample of 152 children with disabilities from various educational and social institutions across North Macedonia, the study employs rigorous quantitative methods, including t-tests and correlation analyses, to explore the relationships between these children’s experiences of violence and their religious and cultural backgrounds. The findings reveal a statistically significant correlation (r = 0.47, p < 0.01) between the degree of religious conservatism in communities and the incidence of violence against children with disabilities, indicating that cultural and religious norms play a critical role in their vulnerability. Moreover, the research identifies a significant difference (t = 2.86, p < 0.05) in the level of secondary traumatization between children who receive support from their religious communities and those who do not. This highlights the potential protective effect of community support in mitigating the harmful impacts of violence. The study underscores the importance of considering the complex interplay of disability, religion, and cultural context when developing interventions aimed at safeguarding vulnerable children from violence and its enduring consequences. These insights are crucial for informing policy and practice in social work, particularly in multicultural settings like North Macedonia.
Keywords: Violence against children, children with disabilities, primary and secondary traumatization, religion, multiculturalism